How analytical hierarchy process prioritizing internet banking influencing factors? a research study - Aziz, Khairi Azhar; Abdullah, Salfarina; Jabar, Marzanah A.; Haizan Nor, Rozi Nor; Ismarau Tajuddin, Nur Ilyana (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Internet banking is a method for conducting financial transactions online that makes use of the internet as a platform. Customers could transact at any time and from any location. Numerous aspects relating to the adoption of internet banking have been analyzed and studied in recent in-depth studies from the literature. This paper will merge these numerous predefined factors into a model by drawing on the various ideas related to the acceptance model. It was decided to adapt the analytical hierarchy process (AHP) method for finding the important numerous components for the model. The finest mathematical calculation method is AHP, which enables decision-makers to prioritize their ranking in order to satisfy various criteria. The goal of this research is to rank the elements that influence the use of online banking. Three main factors such as technical information, website and service availability were chosen as the main factors of the model based on the literature review. Sub-factors such as ease of use, responsiveness, privacy, reliability, security, communication and efficiency were also suggested and combined into a single integrated framework. Utilizing the systematic literature review (SLR) methodology, several factors were found. As a result, the article will enhance understanding of the unique elements supporting the adoption of internet banking.